2020
DOI: 10.31676/2073-4948-2020-63-137-145
|View full text |Cite
|
Sign up to set email alerts
|

Results of Studying Clonal Apple Rootstocks in Different Ecological Conditions of the Volga-Ural Region

Abstract: Реферат. В статье представлены данные по испытанию клоновых подвоев, которые проводились в условиях Южного Урала (г. Оренбург) в течение 30 лет, в Среднем Поволжье (г. Самара) -20 лет, в Ботаническом саду ОГУ -более 10 лет, в Бузулукском бору (с. Партизанское) -более 10 лет. Объектами исследования служили клоновые подвои различных учреждений: кафедры плодовод-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…An important factor in the development of the root system of clonal rootstocks is influenced by the type of substrate for hilling, which improves the mechanical properties of the soil in uterine plantings and enhances the rooting processes of cuttings [13]. Having monitored domestic and foreign scientific works over the past 20 years, they revealed that it is necessary to use substrates on an intensive mother liquor of clonal apple rootstocks to increase productivity [14][15].…”
Section: Introductionmentioning
confidence: 99%
“…An important factor in the development of the root system of clonal rootstocks is influenced by the type of substrate for hilling, which improves the mechanical properties of the soil in uterine plantings and enhances the rooting processes of cuttings [13]. Having monitored domestic and foreign scientific works over the past 20 years, they revealed that it is necessary to use substrates on an intensive mother liquor of clonal apple rootstocks to increase productivity [14][15].…”
Section: Introductionmentioning
confidence: 99%